Gender Representation in English Language Textbooks of Primary Education - Ankur Nandi; Tarini Hader; Tapash Das (Journal of English as A Foreign Language Teaching and Research, 2024)
Textbooks are carriers of social change. It is through textbooks and classroom experiences that from the stage of childhood in the school itself, students start learning to accept gender socialization, social norms, beliefs, gender roles, inequality, and bias. Hence, the need to make the textbooks gender neutral arises becausetheir analysis is necessary for this; it is in this light that the present study has analyzed English textbooks at the primary level of education in India toexaminethe incubation of gender stereotypes and bias. These were coupled with content analysis and qualitative and documentary research. The major findings reflect that gender patriarchy and bias are reflected in English textbooks.Overall, the results indicated that males were more prominently featured in textbooks, both in images and in text. Females were still underrepresented, had fewer diverse occupations, and were often depicted doing household chores in three textbooks. However, there were some positive portrayals and efforts to challenge stereotypes, with examples of gender-neutral language and activities shared by both genders.The findings of this study can also be used to shape policies at the state or national level in creating and applying guidelines for gender-neutral content in educational materials. These guidelines would guide the efforts of a textbook development agency,writers, and teachers in creating gender-sensitive curricula and textbooks.